Effect of recycled molybdenum tailings on mechanical properties of ultra-high-performance concrete - Li, Xin; Liu, Cun-Xiang; Zhao, Xin-Yu; Kang, Shao-Bo (Frontiers in Materials, 2024)
This paper presents experimental studies on mechanical properties and micro-structures of ultra-high performance concrete (UHPC) made of recycled molybdenum tailings. The particle size distribution and chemical compositions of recycled molybdenum tailings were analysed at first. Then, compressive and flexural tests were conducted on UHPC in which different volume fractions of recycled molybdenum tailings were used to replace silica sand. The effects of recycled molybdenum tailings replacement ratio on the compressive and flexural strengths were determined through comparisons. Besides, X-ray diffraction tests and backscattered electron tests were carried out to analyse the effect of molybdenum tailings on the micro-structure of UHPC. Based on test data, an optimal replacement ratio of molybdenum tailings was determined which could significantly reduce the cost of UHPC but maintain the mechanical properties in compression. A molybdenum tailings replacement ratio of 30% was recommended to maximise the economic effect and to reduce the carbon emission.